Peningkatan Penulisan Cerita Pendek Menggunakan Metode Copy The Master Siswa Kelas IX SMP Negeri 5 Mandai Kabupaten Maros - Muhammad Rezky; Badruddin Kaddas; Herawati Arief S; Syukriady, Dwi (AIJER: Algazali International Journal Of Educational Research, 2024)
The aim of this research is the Copy The Master Method's efforts to improve short story writing for Grade 9 Students of SMP Negeri 5 Mandai, Maros Regency. The type of research used is classroom action research. The implementation procedure in this research went through 2 cycles consisting of several stages, namely the planning, implementation, observation and reflection stages. Based on the results of research conducted, the average score of students' short story writing skills from cycle I was 68.7%, then increased in cycle II, namely 73.4%. Student activity or student attitudes during learning have also increased. This can be seen from several aspects observed, namely, students who observed learning in cycle I to cycle II were 61%, students who asked questions during learning in cycle I to cycle II were 56%, students who practiced during learning in cycle I to cycle II 65%, students who understood during learning in cycle I to cycle II were 70%.